Analisis Penerapan Unsur Intrinsik Teks Cerita Anak dalam Pembentukan Karakter Siswa: Analysis the Application of Intrinsic Elements of Children's Story Texts in the Formation of Student Character - Fitriani, Nurul Huda; Handayani, Noor Fazariah; Kamiliya, Nur Salsabila (Anterior Jurnal, 2025)
Based on interviews with the second-grade teacher at SDN 1 Tambang Ulang, Tanah Laut Regency, it was found that students there have difficulty understanding the application of the content of a story, which leads to challenges in applying it to their daily lives. The learning process so far has only focused on identifying intrinsic elements of the story without linking them to the development of character traits relevant to students' everyday lives. This study aims to investigate the application of intrinsic elements of children's story texts in shaping student character at SDN 1 Tambang Ulang. The research uses a qualitative method. The informants in this study were the school principal and the second-grade teacher. Data collection tools used were observation and interviews. After analyzing the collected data, the findings show that the teacher applies two methods—repetition and individual approach—to help students who have not yet grasped the story's content. Additionally, the teacher encourages students to adopt positive character traits from the story and connect these traits with their daily habits at home.